Job Performance among Overtime Employees at Shipyard Industry: Structural Equation Model of Motivation, Hygiene Factors, and Job Satisfaction - Masyhuri, Muhammad; MEISKE CLAUDIA (International Journal of Economics, Business, and Entrepreneurship, 2026)
The objective of this study was to analyze factors that affecting job performance based on Herzberg’s two-factor theory among employees who worked overtime at shipyard industry. The study employed an explanatory research design and cross-sectional design. The total sample was 104 employees working, who were selected through random sampling. The endogenous variable was job performance, the exogenous variables were motivation and hygiene factors, and the mediator was job satisfaction. The data were analyzed using Structural Equation Modeling (SEM) – Partial Least Squares (PLS). The study's results showed that the motivation and hygiene factor had a positive and significant effect on Job Performance. In addition, job satisfaction had a positive and significant effect on job performance. Furthermore, job satisfaction mediated the relationship between motivation factor and job performance, as well as the relationship between hygiene factor and job performance. These findings implied that companies needed to pay attention to incentives (hygiene) and good working conditions (motivation).